Awareness and attitudes towards common mental health problems of community members in Udupi Taluk, Karnataka: A mixed method study - Monica Sindhu; Sameer Phadnis; Zakariya Chouhan; Pallavi Saraswat; Sneha Maheshwari (Elsevier, 2021)
Introduction: The aim of the present study was i) to quantify the awareness about common mental health problem, ii) to assess attitude of community members and healthcare providers towards mental health patients and identify the factors contributing to their stigma and iii) to assess perception of health care providers about National Mental Health Program in Udupi Taluk, Karnataka. Material and methods: A mixed method observational study was done, in 212 community members of above 18 years of age through two-stage cluster sampling. Participants were presented with 2 vignettes defining individuals suffering from symptoms of mental disorders (psychosis and depression) and in-depth interviews were conducted from healthcare providers (n = 11). Descriptive statistics were calculated by bivariate statistical analysis to describe the responses to the variables from the questionnaire. Result: The most commonly recognized causes of the mental health problems were unemployment, separated or divorced, among other socioeconomic factors. Psychiatrist and physician were believed to be the most helpful for providing treatment of mental health problems. The discrimination of people with a mental illness diagnosis of psychosis (74.8%) was more as compared to depression (25.2%). The stigmatizing attitude was found to be more in males (22.3%) of social distancing as compared to females (8.47%). Conclusion: More than 60% of the community members have knowledge and awareness about causal factors of mental health problems in this region. However, there is a need to raise awareness in the community about the National Mental Health program, and services provided by the government for mental health problems.